Graphic calculators in the classroom: Students’ viewpoints - Ponte, João Pedro da (2011)
This paper presents the results of a study about the views and attitudes of students of a low achieving 11th grade class who were involved in an innovative experience with graphic calculators for all academic year. Contrasting the results obtained from a questionnaire and from interviews, it concludes that students tended to point some improvements in the mathematics class, but attributed their origin more to their teacher’ style and personality than to the use of this technology.